Predicting the impact of mutations on the specific activity of Bacillus thermocatenulatus lipase using a combined approach of docking and molecular dynamics. Issue 10 (14th April 2016) - Yukselen, Onur; Timucin, Emel; Sezerman, Ugur
Abstract : Lipases are important biocatalysts owing to their ability to catalyze diverse reactions with exceptional substrate specificities. A combined docking and molecular dynamics (MD) approach was applied to study the chain‐length selectivity of Bacillus thermocatenulatus lipase (BTL2) towards its natural substrates (triacylglycerols). A scoring function including electrostatic, van der Waals (vdW) and desolvation energies along with conformational entropy was developed to predict the impact of mutation. The native BTL2 and its 6 mutants (F17A, V175A, V175F, D176F, T178V and I320F) were experimentally analyzed to determine their specific activities towards tributyrin (C4) or tricaprylin (C8), which were used to test our approach. Our scoring methodology predicted the chain‐length selectivity of BTL2 with 85.7% (6/7) accuracy with a positive correlation between the calculated scores and the experimental activity values ( r  = 0.82, p  = 0.0004). Additionally, the impact of mutation on activity was predicted with 75% (9/12) accuracy. The described study represents a fast and reliable approach to accurately predict the effect of mutations on the activity and selectivity of lipases and also of other enzymes. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A combined docking and molecular dynamics approach was applied to study the chain‐length selectivity of Bacillus thermocatenulatus lipase (BTL2) towards triacylglycerols (tributyrin (C4) or tricaprylin (C8)). The native BTL2 and its six mutants were experimentally analyzed. Our scoring methodology predicted the chain‐length selectivity of BTL2 with 85.7% (6/7) accuracy. The described study represents a fast and reliable approach to accurately predict the effect of mutations on the activity and selectivity of lipases and also of other enzymes.